Shear Lag Effect in Framed-Tube Buildings Due to Torsional Wind Load - Singh A.; Gaikwad P.; Mandal S. (My University, 2025)
Wind load causes shear lag in high-rise tubular buildings. A building’s stability may be adversely affected by this phenomenon when tension inevitably develops in upper story columns. The amount of shear lag depends on several factors, such as the building layout, the spacing between the outer peripheral columns, and the load applied to the building. The shear lag effect must therefore be accurately analyzed by considering these factors. This paper attempts to study the effect of torsional wind loads on the shear lag effect. Four wind load cases are adopted from American code (ASCE 7-22) to analyze the wind load effects on a 40-storied RCC tubular building. The results indicate that axial force distribution changes significantly with changes in the loading patterns of the building. Torsion and non-torsional load cases exhibit different unsymmetrical axial force distributions. Load cases with both direction loadings show notable differences in the axial force distribution compared to single-direction loadings. Axial force distributions due to the case of both face loading are unsymmetrical on both sides of the central column. © 2024, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.